ANALISIS STRATEGI PEMASARAN JASA TERHADAP PENYALURAN KREDIT PADA PT. BANK PERKREDITAN RAKYAT (PT. BPR) TALABUMI PANCUR BATU - Sagala, Roslinda (Jurnal Manajemen dan Bisnis, 2010)
PT. BPR Stone Talabumi Pancur one banking services company. Outstanding loans in 2010 fell compared to the year 2011. Decrease due to relatively high interest rate loans and a lack of promotional activities. The problem: Is services marketing strategy (pricing and promotion) have a signiï¬cant eï¬ect on the amount of outstanding loans. Hypothesis: service marketing strategy (pricing and promotion) have a signiï¬cant eï¬‚ect on the amount of outstanding loans. The purpose of the study, to determine the ejï¬zct of the marketing strategy of lending services. Benefits, as input in further research. The study population is a marketing strategy services and the amount of credit supplied by PT. BPR Talabumi Pancur Stone began to stand up to this research. The samples taken from the year 2001 - 2005 (per semester). Data collection techniques used in this study is the documentation. Analysis technique used is multiple linear regression to determine the eï¬‚ect of service marketing strategy (pricing and promotion) of lending. Based on the results if the discussion was concluded that multiple linear regression equation obtained was Y = 334,146,977.205 to 28,065,996.867 14.628 X1 + X2. This means that services marketing strategy (pricing and promotion) have an inï¬‚uence on lending to the PT. BPR Pancur Talabumi Stone, this can be seen on the regression coeï¬‚icients. Determinant of the coeï¬‚icient of 0.965, meaning that credit can be explained by service marketing strategy (pricing and promotion) of 96.5% while 3.5% more explained by other factors. Based on the results obtained by analysis of F-count = 95.899> F-table 4.74, so H0 is rejected and H1 accepted. This means that services marketing strategy (pricing and promotion) have a signiï¬cant qfect on the number of simultaneous outstanding loans to the PT. BPR Pancur Talabumi Stone, can be accepted at a signiï¬cance level of 5%. Iudgingfrom the results of the t test, concluded that service marketing strategy (pricing and promotion) have a signiï¬cant ejfï¬act of partialâ€˜ to total outstanding loans at PT. BPR Pancur Talabumi Stone, can be accepted at a signiï¬cance level of 5 %. Judging from the regression coeï¬‚icient is known that the price (interest rate) to give a greater contiibution than the promotion of outstanding loans. Promotional activities conducted by PT. BPR Talabumi Pancur Batu less intense, so that outstanding loans fell in 2005. The advice given to the leadership of PT. BPR Talabumi Pancur Stone is to increase the number of loans extended frequency should be increased promotional activities by advertising in mass media and electronic. Preferably, the head of the bank lowers the interest rate of credit to increase the amount of outstanding loans.